Analisis Risiko Overproduction pada Waste Inventory Menggunakan Metode Value Stream Mapping dan House of Risk (Studi Kasus: PT. Benih Citra Asia Jember) - Shinta Ayu Swasti (Fakultas Teknologi Pertanian, 2026)
Inefficiency at rice seed production process located at PT. Benih Citra Asia Jember Regency are cause by limited storage capacity, this study aims to analyze waste and identify risks in the rice seed packaging process at PT. Benih Citra Asia Jember using the Value Stream Mapping (VSM), Process Activity Mapping (PAM), and House of Risk (HOR) approaches. The main problem identified was the limited storage capacity, which caused material accumulation, bottlenecks, time waste, and decreased production process efficiency. The research was conducted through field observations, interviews, and collection of production process time data from January to March 2026. PAM analysis was used to identify Value Added (VA), Non-Value Added (NVA), and Necessary but Non-Value Added (NNVA) activities, while HOR was used to determine risk priorities and mitigation strategies. The results showed that the total processing time for rice seed packaging reached 394,126.76 minutes, with NNVA activities dominating at 98.68%, while VA activities accounted for 0.59% and NVA activities for 0.73%. The VSM analysis indicated a total lead time of 394,225.91 minutes, showing that the production process was still inefficient. Based on the HOR Phase 1 analysis, five main priority risk causes were identified: limited storage capacity, fluctuating demand, errors in determining process time, final products not meeting company standards, and limited human resource knowledge. The proposed mitigation strategies include implementing a FIFO system, demand forecasting using the moving average or exponential smoothing methods, improving machine maintenance, strengthening quality control, and providing employee training. The implementation of these improvement strategies is expected to reduce waste, improve process flow efficiency, and increase the productivity of the rice seed packaging process in the company.
Finalisasi 23 Juli 2026 Rudi H
Keywords: HOR; PT BCA; Rice Seed Packaging Process; VSM; Waste Analysis.